Sensitivity and Feasibility Analysis of Citronella Oil Business - Bimantio, Mohammad Prasanto; Wardoyo, Anthonius Dhinar Hasto (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 14 No 2 (2020): Vol.14.No 2, 2020DO - 10.24843/SOCA.2020.v14.i02.p11, 2020)
Today, citronella essential oil business in Indonesia is fronting two major problems: a diverse range of product quality and fluctuated price. Meanwhile, the global market demand keeps increasing until 3–5% per year. This fact indicated that the citronella essential oil business was having a high chance of participating in the global market. This study aimed to analyze the citronella essential oil business feasibility as a “people-oriented-economy” activity and determine variables that affected the feasibility in implementing this business. Citronella essential oil is produced by a steam distillation process with a production capacity of 2,400 kg/year. The number of citronella essential oil international product sales was reaching 76% with the selling price of IDR 360,000/kg and reaching 24% on the local market with the selling price of IDR 180,000/kg, therefore the total of sales in 300 days/year was IDR 7,360,320,000. Based on this calculation the total of profit obtained in a year was IDR 99,463,383. An effort through managing the material and selling price sensitivity already done to maintain the BEP and B/C values. The increasing price was anticipated by managing the product selling price fraction, while the decreasing of the selling price anticipated by managing the market fraction.